Sensory processing issues in children with cerebral palsy: a pilot study in tertiary care institute - Gaurav, Kunal; Kumar, Raj; Kumar, Ganesh; Gupta, Anand Kumar; Runu, Ritesh; Singh, Abhinav (International Journal of Contemporary Pediatrics, 2023)
Background: Understanding of sensory processing disorder in children with cerebral palsy is paramount to implement holistic rehabilitation and it would help in achieving highest level of function and independence. The purpose of the study was to detect sensory processing disorder in children with cerebral palsy in east zone of India. This study may help to formulate the implementation of effective therapy protocol in east zone. Methods: The study was a prospective cross-sectional study.30 children with cerebral palsy were enrolled in our study. All 30 children were spastic diplegic. Children were assessed with short sensory profile. All caretakers were given questionnaire of SSP (short sensory profile). Results: Short sensory profile can help find out the sensory processing disorder in cerebral palsy. All 30 participants showed sensory processing difficulties in at least one of the sensory processing sections. In our study, 19 children with cerebral palsy out of 30 showed sensory processing disorder. 22 children with cerebral palsy have reported sensory seeking issue and same number of kids has reported weak muscles and low endurance. Moreover, 18 of the children with cerebral palsy have reported movement sensitivity issue and 6 children reported visual auditory issues. On top of that 15 children with CP have reported auditory filtering issues, 9 children showed tactile sensitivity issues and 11 children showed taste and smell sensitivity. Conclusions: Children with spastic diplegic cerebral palsy showed difficulty in sensory processing especially in sensory seeking domain. Sensory processing disorder is present in children with cerebral palsy.